A escuta das relações familiares na clínica psicanálitica individual - Vaz, Regina Márcia Manicardi (2013)
The present research aims to study, as part of the analytic listening, the family relationships present in the psyche of the patient treated individually. To achieve this purpose, it was developed a systematization of the theoretical content of the psychological aspects of family group functioning, concerning the participation in the psyche of its members. A systematization of some elements of psychoanalytic clinic was also carried out, particularly the listening, the transference and the countertransference. From the methodological point of view, we compiled theoretical considerations that turned the logic of our goal more consistent. The development of the work focused on three central themes presented in three chapters. In the first one, the highlight was the intersubjective nature of the psychic constitution. For this, we used as main reference Kaës, focusing on group dimension in the individual subject, and Winnicott, on the importance of the primary relationship mother / baby (and family) in the psyche constitution. In the second chapter, we discussed the clinic from a listening that considers the family group aspects of the patient treated individually. In this respect, we made a brief consideration on clinic today, highlighting the events that reveal some depletion of the symbolic capacity. Then we discussed about some elements that define the space / clinical field, addressing mainly the perspective of the evolution of these concepts in the history of psychoanalysis. In the third chapter, we discussed about some of the group elements of psychic constitution that can be listened in individual treatment. We used fragments of cases to illustrate this discussion. We believe that this study contributes to a discussion of psychoanalytic clinic from an "expanded listening", a listening that enhances the subject who is constituted in the family.